2009
DOI: 10.1007/s12088-009-0035-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pulmonary tuberculosis (PTB) among people living with HIV/AIDS (PLWHA) in Keffi and its environs

Abstract: Coinfection with HIV and Mycobacterium tuberculosis is known to be a lethal combination especially with its attendant mortality and morbidity. The need to have a baseline data in an environment like Keffi with a HIV/AIDS prevalence of 38.6% necessitated this study. Three hundred and ninety people living with HIV/AIDS (PLWHA) were screened for pulmonary tuberculosis. Results of this study showed 16.7% prevalence of coinfection in the population. Gender-related prevalence of coinfection was 19.4% and 14.4% among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 9 publications
2
2
0
Order By: Relevance
“…We found no association between gender and the prevalence of tuberculosis on the population studied (X 2 = 0.02; p > 0.05) with prevalence in males and females put at 21% and 18%, respectively. This finding is in conformity with other studies (27,28,33,36) that looked at the effect of gender on the prevalence of TB on people living with HIV. Pennap et al (28) reported no significant difference in prevalence of TB in males (19.4%) and females (14.4%) co-infected with HIV in Keffi, in Nigeria, suggesting gender plays no role in prevalence of TB in people living with HIV.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found no association between gender and the prevalence of tuberculosis on the population studied (X 2 = 0.02; p > 0.05) with prevalence in males and females put at 21% and 18%, respectively. This finding is in conformity with other studies (27,28,33,36) that looked at the effect of gender on the prevalence of TB on people living with HIV. Pennap et al (28) reported no significant difference in prevalence of TB in males (19.4%) and females (14.4%) co-infected with HIV in Keffi, in Nigeria, suggesting gender plays no role in prevalence of TB in people living with HIV.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in conformity with other studies (27,28,33,36) that looked at the effect of gender on the prevalence of TB on people living with HIV. Pennap et al (28) reported no significant difference in prevalence of TB in males (19.4%) and females (14.4%) co-infected with HIV in Keffi, in Nigeria, suggesting gender plays no role in prevalence of TB in people living with HIV. Although we found no significant association of age (P > 0.05) with the prevalence of TB in people living with HIV, there was general increase in the prevalence of tuberculosis as the age progresses with the age group between 61 and 70 recording the highest proportional distribution.…”
Section: Discussionsupporting
confidence: 92%
“…is has been shown in several studies in different countries [15][16][17]. However, this prevalence is much higher than that reported in Keffi Northcentral Nigeria [18] which showed 16.7% prevalence of HIV positivity in tuberculosis patients. e high prevalence in our study may be due to the fact that we routinely screen all TB patients for HIV in the DOTS clinic.…”
Section: Discussionmentioning
confidence: 76%
“…Five (1.25%); 4 M. bovis and one M. africanum from 400 unpasteurized milk samples from north-central Nigeria were positive because drinking unpasteurized milk is a usual practice of some Nigerians [10] their report emphasizes that transmission between the animal and human reservoir is a serious threat [17]. Importance of tuberculosis in Nigerian patients infected with HIV has been previously reported [18,19]. In another similar study, the prevalence of M. tuberculosis in people living with HIV in Osun state of Nigeria was found to be 25% using microscopy, 15% and 18.75% for M. tuberculosis and M. tuberculosis complex, respectively, suggesting there is overestimation of TB cases using microscopy.…”
Section: Tuberculosismentioning
confidence: 99%